Removal of antimonite (Sb(iii)) and antimonate (Sb(v)) using zerovalent iron decorated functionalized carbon nanotubes. Issue 98 (7th October 2016) - Mishra, Shruti; Dwivedi, Jaya; Kumar, Amar; Sankararamakrishnan, Nalini
Abstract : Zerovalent iron decorated CNTs exhibited excellent adsorption capacity towards both Sb(iii ) and Sb(v ). Using XPS, FTIR and Raman mechanism of interaction is postulated. Abstract : Carbon nanotubes (CNT) were synthesized by floating catalytic chemical vapor deposition method using ferrocene and benzene as hydrocarbon source. The prepared CNTs were oxidized with nitric acid (CNT-OX) followed by coating with nano zerovalent iron (ZVI) to yield nano ZVI decorated CNTs (CNT-Fe(0)). The prepared adsorbents were characterized by various techniques. Using spectral techniques like infra red, Raman and X-ray photoelectron spectroscopy, the mechanism of adsorption between the adsorbent and adsorbate has been postulated. Using CNT-Fe(0) at pH 5, the maximum adsorption capacity of Sb(iii ) and Sb(v ) was found to be 250 mg g −1 . The high sorption capacity could be attributed to the high surface area of the prepared CNTs and the reactive nature of the nano zerovalent iron particles on CNTs. A pseudo second order kinetics was followed by CNT-Fe(0) with both Sb(iii ) and Sb(v ) with a rate constant of 0.0015 and 0.0011 mg g −1 min −1 respectively. The interference effect of various ions on the adsorption of Sb(iii )/Sb(v ) are as follows: PO4 3− > SiO3 2− > ASO4 3− > SO4 2−, NO3 − > Cl −, humic acid. The recyclability of the sorbent was demonstrated for 5 cycles using 0.05 M HCl as desorbent. The versatility of the adsorbent was demonstrated by the removal capacity of both Sb(iii ) and Sb(v ) at parts per billion levels from nuclear decontamination formulation (NAC) and tap water matrix as well.